Respuesta :
If you would like to know which subtraction expression has the difference 1 + 4i, you can calculate this using the following steps:
a. (–2 + 6i) – (1 – 2i) = –2 + 6i – 1 + 2i = –3 + 8i
b. (–2 + 6i) – (–1 – 2i) = –2 + 6i + 1 + 2i = –1 + 8i
c. (3 + 5i) – (2 – i) = 3 + 5i – 2 + i = 1 + 6i
d. (3 + 5i) – (2 + i) = 3 + 5i – 2 – i = 1 + 4i
The correct result would be d. (3 + 5i) – (2 + i).
a. (–2 + 6i) – (1 – 2i) = –2 + 6i – 1 + 2i = –3 + 8i
b. (–2 + 6i) – (–1 – 2i) = –2 + 6i + 1 + 2i = –1 + 8i
c. (3 + 5i) – (2 – i) = 3 + 5i – 2 + i = 1 + 6i
d. (3 + 5i) – (2 + i) = 3 + 5i – 2 – i = 1 + 4i
The correct result would be d. (3 + 5i) – (2 + i).